A 41-year-old male with generalized hyperpigmentation and weakness: “Histoplasmosis- a mimic of tuberculosis” - Jahan, Sharmin; Rijal, Amrit; Fakhrul-Alam, Mohammad; Hossain, Md Solaiman; Sultana, Nusrat; Hasanat, Muhammad Abul; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
A 41-year-old man with diabetes mellitus and smoking history was initially treated for tuberculosis (TB) based on clinical and radiological findings despite a negative sputum test. However, his treatment was interrupted by jaundice and an adrenal crisis. Further testing revealed that he had disseminated histoplasmosis involving the liver and adrenal glands. He was partially improved with antifungal and steroid therapy. This case highlights the difficulties in distinguishing between these two diseases and the need for a high index of suspicion and cytological confirmation for accurate diagnosis and treatment. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2025;4(2): 85-89